Radioaktywne skażenie składu pokarmu sarny europejskiej Capreolus capreolus na terenie Żytomierskiego Polesia Ukrainy - Krasnov, Volodymyr; Boiko, Sergii; Gulik, Igor; Shelest, Zoia; Sieniawski, Waldemar (Leśne Prace Badawcze, 2015)
This paper presents a study on radioactive contamination of dietary components of the roe deer ( Capreolus capreolus ) in Zhytomirske Polesie (Ukraine). Studies were conducted on two research plots in forests with similar levels of radioactive contamination, 29 ± 8 kBq/m 2 – 55 ± 17 kBq/m 2 , in mixed coniferous forests and mixed broadleaved forests, which are the dominant forest types of the area. The highest level of radionuclide accumulation was observed in young oak seedlings. The dynamics for oak sprouts indicate that the accumulation coefficient reaches a maximum in September and August in the mixed coniferous and mixed broadleaved forests respectively. A comparison of mean values of the 137 Cs accumulation coefficients in the shoots of undergrowth plants confirms that an increase in soil fertility leads to a reduction of radionuclides in plant phytomass. In the mixed broadleaved forests, average values of the coefficient of 137 Cs accumulation in phytomass of blackberry was 26% and of raspberries 58% lower compared to mixed coniferous forests. The maximum contamination of phytomass was observed in August for oak, in October for aspen, and in July for birch. The highest specific activity of 137 Cs in raspberry shoots occurs during the three summer months, whereas the peak in blackberry occurs from August to September. The dynamics of the specific activity of 137 Cs in blueberry, cranberry and heather show an increase in radioactive contamination of phytomass towards the end of the growth period. The maximum concentration of 137 Cs in shoots of heather and bilberry was recorded in October and for blueberry in August. Mushrooms in mixed coniferous forests can be ranked as follows according to the degree of 137 Cs contamination: Cantharellus < Boletus edulis < Russula < Leccinum < Xerocomus badius < Paxillus involutus. In mixed broadleaved forests the ranking is Cantharellus < Boletus edulis < Russula < Xerocomus badius < Leccinum < Paxillus involutus . Within one habitat type, we observed fairly significant variations in 137 Cs accumulation in fruit bodies of fungi species.